DFT Calculations and Molecular Docking Studies on a Chromene Derivative - Najet Aouled Dlala; Younes Bouazizi; Houcine Ghalla; Naceur Hamdi (Journal of Chemistry)
Chromenes and their derivatives have been considered as an important class of oxygen-containing heterocycles. There has been an increasing interest in the study of chromenes due to their biological activity. Herein, the structural, electronic, and vibrational properties of a chromene derivative, entitled 2‐amino‐5‐oxo‐4‐phenyl‐4,5‐dihydropyrano[3,2‐c]chromene‐3‐carbonitrile and abbreviated as Chrom-D, have been reported. The FT-IR, UV-vis, and 1H-NMR and 13C-NMR chemical shifts’ measurements were recorded. The molecular geometry and the vibrational frequencies are computed in the frame of density functional theory at the B3LYP/6-311++G(d,p) level of theory. The noncovalent interactions in the crystal lattice which are responsible to the 3D crystal structure of Chrom-D are investigated based on Hirshfeld surfaces and topological reduced density gradient (RDG) analysis. Molecular electrostatic potential surface, Mulliken charges, and Fukui functions are computed in order to find out the electrophilic and nucleophilic sites. The electronic properties of the title compound have been studied based on the TD-DFT calculations. Finally, Chrom-D has been evaluated as a multifunctional agent against Alzheimer’s disease (AD).